2019
DOI: 10.1021/jacs.9b06277
|View full text |Cite
|
Sign up to set email alerts
|

Driving Recursive Dehydration by PIII/PV Catalysis: Annulation of Amines and Carboxylic Acids by Sequential C–N and C–C Bond Formation

Abstract: A method for the annulation of amines and carboxylic acids to form pharmaceutically relevant azaheterocycles via organophosphorus P III /P V redox catalysis is reported. The method employs a phosphetane catalyst together with a mild bromenium oxidant and terminal hydrosilane reductant to drive successive C–N and C–C bond-forming dehydration events via the serial action of a catalytic bromophosphonium intermediate. These results demonstrate the capacity of P … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 59 publications
(20 citation statements)
references
References 67 publications
1
19
0
Order By: Relevance
“…Recent innovations in synthetic organophosphorus chemistry are fueling new opportunities for catalysis. 1 As a complement to well-known nucleophilic (Lewis basic) reactivity, 2 new structural design principles are emerging that now enable organophosphorus catalysis to comprise Lewis acidic, 3 dehydrative, 4 redox O-atom transfer, 5 and reductive 6 activation modes for catalysis. Within this vein, nontrigonal phosphorus triamide 1 (ref.…”
Section: Introductionmentioning
confidence: 99%
“…Recent innovations in synthetic organophosphorus chemistry are fueling new opportunities for catalysis. 1 As a complement to well-known nucleophilic (Lewis basic) reactivity, 2 new structural design principles are emerging that now enable organophosphorus catalysis to comprise Lewis acidic, 3 dehydrative, 4 redox O-atom transfer, 5 and reductive 6 activation modes for catalysis. Within this vein, nontrigonal phosphorus triamide 1 (ref.…”
Section: Introductionmentioning
confidence: 99%
“…This behavior inspired the development of phosphetane oxide 3 – 11 -catalyzed didehydration for the preparation of functionalized heterocyclic adducts (Scheme ). The annulation was amenable to both aniline and benzylamine for the construction of six- and seven-membered rings. The key to the success of this sequential annulation is the generation of the halophosphonium cation 3 – 29 from the in situ-generated phosphetane and the oxidant diethyl bromomalonate (DEBM).…”
Section: Phosphine Oxide Catalysismentioning
confidence: 99%
“…Several research groups have reported the synthesis of 4-aryl pyrrolo­[1,2-α]­quinoxalines from benzyl amine instead of aldehyde . In addition, the condensation of 1-(2-aminophenyl)-pyrrole with ketone, carboxylic acid, 1,3-diketone, amino acid, or ether was also reported for the synthesis of 4-aryl pyrrolo­[1,2-α]­quinoxalines. Although the various synthetic methods mentioned above have provided 4-aryl pyrrolo­[1,2-α]­quinoxalines, they also involve an electrophilic carbon synthon with specific functional groups such as carbonyl, hydroxyl, and amine groups, which limits the substrate scope.…”
Section: Introductionmentioning
confidence: 99%